SCIENTIFIC AND METHODOLOGICAL, SPIRITUAL AND MORAL GUIDELINES IN MANAGEMENT TRAINING AT THE STATE UNIVERSITY OF MANAGEMENT (PART 2) - A. M. Ljalin; V. A. Persianov; V. I. Korolevskaja (Вестник университета)
The article is a continuation of an article of the same name published in the journal “Vestnik Universiteta” № 12 2019. Presented part is devoted to methodological problems, systemic approach in management and development of guidelines in setting scientific research. The systemic approach has been chosen as a fundamentally new level of thinking culture. It allows you to take into account many conditions of internal and external environment. Particularly importance is attached to the ideological dimension. Moral qualities of the person, priority of national interests should become the basis of the world view of future specialists. Educational work, like training, must be continuous. The development of the university concept of student education has necessitated a paradigm shift in the methodology of scientific development. The most important problems of training management personnel in universities of Russia have been formulated in the article